Histology of the digestive tract of Satanoperca pappaterra (Osteichthyes, Cichlidae) - doi: 10.4025/actascibiolsci.v34i3.8956 - Norma Segatti Hahn; Maria Raquel Marçal Natali; Marlene Rodrigues da Silva (Acta Scientiarum: Biological Sciences, 2012)
the esophagus, stomach and intestine of Satanoperca pappaterra using histological techniques. The species presents detritivore-invertivore feeding habit and is widely distributed in Neotropical continental waters. The esophagus is short, the stomach is small with saccular form and the intestine is long. The histological sections were stained using hematoxylin/eosin and Periodic Acid Schiff. Throughout the digestive tract, the gastric wall is composed by four different tunicae: mucosa, submucosa, muscularis externa and serosa, besides distinct intrinsic innervation represented by the submucosal and myenteric ganglionated plexuses. Depending on the organ, several characteristics were peculiar such as the external muscle layer of the esophagus that permeates the submucosa; a single sphincter between the stomach and intestine; stomach without differentiated regions; intestine histologically and physiologically divided into two regions (proximal and distal), considering the villi height and spacing besides the density of the goblet cells.